The Book Chamber of the Chuvash Republic as the Custodian of the Writing and Ethnic Culture - Tikhon S. Sergeev (Publishing house "Sreda", 2022)
The article reveals the history of the creation and main functions of the Book Chamber of the Chuvash Republic (in 2000-2012 - the State Press Archive), which in 2013 became part of the National Library of the Chuvash Republic. The purpose of the article is to reveal the significance of the Book Chamber of the Chuvash Republic as the main center for collecting and storing printed materials about Chuvashia and the Chuvash people, regardless of the place of publication. On the basis of the chronological method, the role of printed materials in the Chuvash language in the preservation of the ethnic culture of the titular people has been studied. It was revealed that the Book Chambers as institutions with a special legal regime existed in 5 points of the Russian Federation: in Moscow, in the republics of Bashkortostan, Tatarstan, Chuvashia and Karelia. Their funds were used in scientific and publishing developments, preparation of materials for publication and for reprints. At present, the main activities of the Department of the Book Chamber are the acquisition, accounting and preservation of the fund of printed documents; state registration of printed documents in the Chuvash Republic, preparation of state bibliographic and statistical information; information and bibliographic services for users; methodological support of editorial and publishing activities of the mass media, publishing and printing enterprises of the republic; creation of a bibliographic database of articles «Chuvashik»; preparation and publication of the state bibliographic index «Chronicle of the press of the Chuvash Republic».